2021
DOI: 10.1002/eap.2287
|View full text |Cite
|
Sign up to set email alerts
|

Recent bark beetle outbreaks influence wildfire severity in mixed‐conifer forests of the Sierra Nevada, California, USA

Abstract: In temperate forests, elevated frequency of drought related disturbances will likely increase the incidence of interactions between disturbances such as bark beetle epidemics and wildfires. Our understanding of the influence of recent drought and insect-induced tree mortality on wildfire severity has largely lacked information from forests adapted to frequent fire. A recent unprecedented tree mortality event in California's Sierra Nevada provides an opportunity to examine this disturbance interaction in histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…Warmer temperatures and increasing aridity have been associated both with increasing drought frequency and intensity (Diffenbaugh et al 2015) and greater frequency and size of wildfires (Westerling et al 2006;Littell et al 2016;Abatzoglou and Williams 2016). Furthermore, drought often triggers bark beetle (Coleoptera: Curculionidae, Scolytinae) outbreaks in conifer forests across the northern hemisphere (Kolb et al 2016;Young et al 2017), and when this combination causes extensive tree mortality, it may alter wildfire hazard, behavior, or resulting fire severity through changes in fuel characteristics (Kane et al 2017;Gray et al 2021;Wayman and Safford 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Warmer temperatures and increasing aridity have been associated both with increasing drought frequency and intensity (Diffenbaugh et al 2015) and greater frequency and size of wildfires (Westerling et al 2006;Littell et al 2016;Abatzoglou and Williams 2016). Furthermore, drought often triggers bark beetle (Coleoptera: Curculionidae, Scolytinae) outbreaks in conifer forests across the northern hemisphere (Kolb et al 2016;Young et al 2017), and when this combination causes extensive tree mortality, it may alter wildfire hazard, behavior, or resulting fire severity through changes in fuel characteristics (Kane et al 2017;Gray et al 2021;Wayman and Safford 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, slower‐growing vegetation, including evergreen needleleaf forests, are less responsive to variability of precipitation in the growing season, and flammability is more controlled by longer‐term periods of dry conditions and drought. Drought also promotes tree death by bark beetles, which can influence burn severity, especially when coupled with additional weather stressors (Wayman & Safford, 2021), although the effect of bark beetles also remains contested (Hicke et al, 2012; Jolly et al, 2012). Nuances in terms of short‐ and long‐term predictors are also expected to produce varying patterns of fire burn severity.…”
Section: Introductionmentioning
confidence: 99%
“…We found that surface fire probability and severity only responded to beetle outbreaks when mortality was higher than 10% and stopped increasing at around 50% during the old phase. Similarly, based on field observations in mixed-conifer forests in the Sierra Nevada, Wayman and Safford (2021) reported that fire severity increased most substantially when beetle-caused mortality surpassed 15% and was below 30%-40%. In this study, fire severity may have stopped increasing with mortality above 50% because plant water demand decreased, leading to decreases in fuel aridity.…”
Section: The Effects Of Tree Mortality On Fire Responsesmentioning
confidence: 98%
“…While the conceptual framework outlined above is useful for understanding temporal wildfire responses to beetle outbreaks, several uncertainties still remain (Halofsky et al., 2020; Hicke et al., 2012). For example, in the gray and old phases, many field observations (Bebi et al., 2003; Berg et al., 2006; Lynch et al., 2006) and modeling studies (Ager et al., 2007; Lundquist, 2007; Meigs et al., 2016) have documented decreases or no change of fire probability and fire severity, while others have found increases (Bigler et al., 2005; Turner et al., 1999; Wayman & Safford, 2021). These increases in crown fire severity during the gray phase may have occurred because once the canopy opened, more radiation was able to penetrate, and competition for resources decreased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation